Deaths from COVID-19 in Spain during the ‘first wave’: Quantitative data and its journalistic treatment - Cobarsí Morales, Josep; Calvet Liñan, Laura; Segundo Martín, Elena (Revista General de Información y Documentación, 2022)
The COVID-19 pandemic has brought controversies regarding the quantification of deaths in many countries. Mainly, discussions were fuelled by the sudden change of the criteria being applied, the limited testing and tracing capacities, and the collapse of the healthcare system. This work analyzes the journalistic treatment for the case of Spain, which is one of the European countries with the highest number of cases and deaths during the ‘first wave’. Firstly, it provides a technical discussion about the coherence, traceability and limitations of available quantitative open data sources. Official data sources (in particular: the Ministry of Health, the Mortality Monitoring System (MoMo) of the National Epidemiology Center and the National Institute of Statistics (INE)) and non-official data sources are considered. Secondly, an analysis of the public discussion on these data is proposed through journalistic coverage by the main national newspapers. An amount of 700 informative pieces are considered and the most used data sources and the evolution of the number of pieces per newspaper are studied, in addition to offering a qualitative approach about the main topics of discussion. Finally, suggestions of improvement and future research are gathered, for the reliability of mortality data as a way to enhance learning and resilience for future crises, their journalistic treatment and their historical record.
Keywords: Data quality; Health crisis; Journalistic coverage; COVID-19; Open data; Quantitative data; Mortality data; Public health data; Data journalism